Transformasi Ekonomi Kreatif di Era Digital: Strategi dan Implementasi Pengembangan Unit Mikro Kecil dan Menengah - Irianto, Okto; Syahrul, Ridho Sefrial; Aziz, Rifqi Aminudin (Insan Kreasi Media, 2025)
Youth entrepreneurship development in Merauke requires synergy among various stakeholders, particularly between the State Treasury Office (KPPN) Merauke as a state financial management institution, and Musamus University as a higher education institution. This community service aims to identify effective collaboration patterns between the two institutions in building a sustainable youth entrepreneurship ecosystem. The method used is Focus Group Discussion (FGD) involving 10 KPPN Merauke employees and 5 Musamus University lecturers. The FGD resulted in three main collaborative programs: ANIM ISAI Digital Program for digital marketing training, SAMKAI Creative Hub for creative business incubation, and MSME financial mentoring program. The division of roles between KPPN as financial supervisor and Musamus University as technical advisor proved effective in designing programs that meet local needs. Key recommendations include establishing a joint coordination team, developing an integrated monitoring system, and preparing technical implementation guidelines. This program can potentially become a model for institutional collaboration in youth entrepreneurship development in the Papua region.